Experimental Study of Renal Tubular Cells Apoptosis Subsequent to Infectious by Influenza Virus (H9N2) in SPF Chickens - Doustar , Yousef; Mohajeri, Daryoush; Anzabi, Younes; Nazeri, Mehrdad (International Journal of Poultry Science, 2011)
Influenza virus produces cell death in animals and human. Since cell death can be caused by either necrosis or apoptosis. We investigated the types of cell death that occur in chickens infected with avian influenza virus, A/chicken/Iran/772/2000(H9N2). In experimental study 60 SPF chickens at 3 weeks old were divided to two groups. The first group was infected with 107.5 EID50 titer of the virus intranasaly and the second group was treated with saline normal. Following 72 hrs, renal tissues were collected and fixed in 10% formalin solution. The prepared microscopic sections with the thickness of 5-6 micron were stained using TUNEL method. In comparison to the control group, there were significant mean difference of apoptotic cells in renal tubular cells of the infected group (p